Acoustic attenuation performance of a round silencer with the spiral duct at the inlet - Łapka, Wojciech (Archives of Acoustics, 2007)
The acoustic attenuation performance of a round silencer with the spiral duct at the inletis investigated. A Finite Element Method was used for a three-dimensional numerical computationsin a COMSOL Multiphysics application. A time-harmonic analysis without airflowwas used for a frequency range from 10 Hz to 2 kHz. The results show that the spiral ductat the inlet can improve the acoustic attenuation performance of a round silencer. The soundattenuation depends on a spiral lead, an absorbing material and frequency. The transmissionloss of investigated acoustic system with spiral ducts is related to an initial acoustic systemwith circular pipe. The results are shown as a growth of transmission loss $Δ$TL given byan insertion of the spiral ducts. A specific parameter given by relation of the spiral lead $s$ toconstant circular duct diameter d is presented as $s/d$ ratio. The value of $Δ$TL is determinedby $s/d$ ratio and increases in specific frequencies. An acoustic wave, in those frequencies, isthere divided at the outlet of the spiral duct and major acoustic energy goes aside, directly toan absorptive material, and minor acoustic energy goes axially to the silencers outlet. This isthe damping effect of the spiral ducts.